Optimization of Pamsimas as A Drought Mitigation in Sidomulyo Village, Ngadirojo District, Pacitan - Madlazim; Fahmi, Muhammad Nurul; Realita, Arie; Ni Made Aprillia Sekar Manggartika (Journal of Dedication in Community, 2024)
This study examines the optimization of the PAMSIMAS (Community-Based Drinking Water and Sanitation Provision) program in Sidomulyo Village, Ngadirojo District, Pacitan, as a proactive strategy to address drought conditions intensified by the village's geographical challenges. This study aimed to achieve two primary objectives: to evaluate the existing water distribution system and to suggest both technical and community-oriented enhancements to secure a more dependable water supply. Field observations and technical analysis indicate that the existing system, dependent on antiquated infrastructure, faces challenges in delivering reliable water access to Ledok Wetan and Ledok Kulon hamlets. To tackle this issue, we suggested the implementation of a booster pump to enhance water pressure and facilitate concurrent water distribution throughout both hamlets. Furthermore, participation from the community in training related to system maintenance and water resource management was promoted to guarantee enduring sustainability. The results indicate that integrating infrastructure enhancements with community education has the potential to enhance water security, offering a framework that may be applied in other drought-impacted areas of Indonesia.